The Rise and Fall of Brazilian Inequality: 1981-2004 - Ferreira, Francisco H.G. (2012)
Brazil's Gini coefficient rose from 0.57 in 1981 to 0.63 in 1989, before falling back to 0.56 in 2004. Poverty incidence rose from 0.30 in 1981 to 0.33 in 1993, before falling to 0.22 in 2004. This paper presents a preliminary investigation of the determinants of Brazil's distributional reversal over this period. The rise in inequality in the 1980s appears to have been driven by increases in educational attainment in a context of convex returns, and by high and accelerating inflation. Although the secular decline in inequality, which began in 1993, is associated with declining inflation, it also appears to have been driven by four structural and policy changes, namely, declining returns to education; pronounced rural-urban convergence; increases in social assistance transfers targeted to the poor; and a possible decline in racial inequality. Falling inequality has made a substantial contribution to poverty reduction.